Prophetic Principles for Global Interfaith Peace: A Comparative Study in the Context of the United Charter - Dr. Muhammad Waqar; Dr. Noman Naeem (`, 2025)
This research article reviews the prophetic principles of five major world religions, including Islam, Christianity, Judaism, Hinduism, and Buddhism, in terms of global inter-faith peace by the United Nations (UN) Charter-related themes. Using sacred texts, historical practices, and contemporary interfaith endeavors to highlight shared ethical and spiritual values compatible with the UN Charter vision of creating conditions for peace, security, and human rights. Qualitative Comparative Analysis is used in this article to reveal aspects of theological, historical, and sociopolitical factors that are most important in conveying nuclear prophetic teachings that are inclusive enough to bring diverse religious communities closer together. The paper reviews the difficulties of cross-religious dialogue, stressing that religiously inspired peacebuilding generally occurs at the level of faith-based organizations, and grassroots action. These results indicate that prophetic values consistent with compassion, justice, and human dignity provide a strong basis to advance the cause of world peace in line with the UN Charter. It concludes by proposing a series of guidelines to assist policymakers, religious leaders, and members of interfaith organizations in conjunction with their efforts to secure sustainable peace. KeyWords: Prophetic Principles, United Nations, Charter, Interfaith Harmony, Peace, Compassion, Justice, Human Dignity, Peacebuilding, Universal Brotherhood